Estrogen, menstrual cycle phases, and psychopathology in women suffering from schizophrenia - Bergemann, Niels; Parzer, Peter; Runnebaum, Benno; Resch, Franz; Mundt, Christoph (Psychological medicine, 2007)
BackgroundEstrogen has been hypothesized to have a protective and antipsychotic-like effect in women at risk for schizophrenia. The aim of the present study was to evaluate the association between menstrual cycle and/or estrogen levels and psychotic symptoms in a sample of women with schizophrenia.MethodOne hundred and twenty-five premenopausal women with schizophrenia and regular menses were examined. The levels of 17β-estradiol and other hormones of the gonadal axis were assessed in the follicular, peri-ovulatory, and luteal phases of the menstrual cycle. The effects of the menstrual cycle phase and/or the estradiol level on the Positive and Negative Syndrome Scale (PANSS) and the Brief Psychiatric Rating Scale (BPRS) scores were calculated by means of regression analyses.ResultsSignificant improvement in psychotic, but not depressive, symptoms was observed during the luteal phase, compared with other days of the menstrual cycle.ConclusionsThe present findings indicate that estradiol may have specific antipsychotic-like effects on the symptoms of schizophrenia. Thus further investigation into the therapeutic effect of estrogen may be worthwhile.
Gesehen am 10.12.2020